KOMUNITAS SEBAGAI INFRASTRUKTUR PERKEMBANGAN SENI GRAFIS DI YOGYAKARTA - Mahendrapati, Alexander Nawangseto (Institut Seni Indoensia Surakarta, 2018)
ABSTRACTThe research was conducted on the basis of there are at least three reasons why the first is, there has been no mapping to the printmaking community in Yogyakarta and their activity. Second, raise awareness college students to forming a community as a receptacle for learning, working, and do the movement of together in independent to develop printmaking. Third, the results of the study to determine the learning methods that continued as an effort to increasing the quality of the artworks of the students are, created the atmosphere at work, to providing the socialization about printmaking to the people. Qualitative descriptive study is used in analyzing the results of observations are done continuously thus obtaining a complete mapping concerning the phenomenon of the growth of the printmaking communities following the influence of existence of them in the development of printmaking in Yogyakarta, and positive values to be adopted or developed further as learning materials for graphic art students the Indonesia Institute of The Arts Surakarta. The result of research conducted in the form of mapping the art community graphic in yogyakarta and recommendations on one method learning with a system of the formation of groups small in the class in the process of the achievement of the creation for students, and a growing spirit to introduce printmaking to the people of Surakarta to become a branches of art popular. Keywords: mapping , community , printmaking, popular.